GENERATION Z’S INTEREST IN USING SHARIA DIGITAL BANKS AS A FINANCIAL SERVICE IN THE ERA OF DISRUPTION - Muharromah, Gabriele Lailatul; Mustofa, Mustofa; Rahmawati, Lilik (Al-Infaq: Jurnal Ekonomi Islam, 2024)
The banking industry is presently undergoing innovation by integrating cutting-edge technology to establish digital banks. A digital bank conducts its operations exclusively online through an application and typically has a central office. In Indonesia, there is a growing popularity of digital banks, with a noticeable emergence of Sharia-based digital banks. However, the progress of Islamic digital banks is comparatively slower when compared to non-Sharia counterparts. Capitalizing on the familiarity of Gen Z with technology, this study aims to explore how the variables of convenience, security, and religiosity individually and collectively influence the inclination of Generation Z in Surabaya to use Islamic digital banks. The research adopts a quantitative approach, specifically causal research, and collects data through online questionnaires distributed via Google Forms. With a sample size of 170 respondents selected through purposive sampling, the study employs SmartPLS 3 software for data processing and analysis. Findings indicate that the convenience variable positively and significantlyimpacts the interest in using Islamic digital banks, while the security variable also exerts a positive and significant influence. However, the religiosity variable does not show a significant effect on the interest in using Islamic digital banks. When considered together, convenience, security, and religiosity collectively influence the interest in using Islamic digital banks.